Sphingolipid Distribution, Content and Gene Expression during Olive-Fruit Development and Ripening - Inês, Carla; Parra-Lobato, Maria C.; Paredes, Miguel A.; Labrador, Juana; Gallardo, Mercedes; Saucedo-García, Mariana; Gavilanes-Ruiz, Marina; Gomez-Jimenez, Maria C. (Frontiers in Plant Science, 2018)
Plant sphingolipids are involved in the building of the matrix of cell membranes and in signalling pathways of physiological processes and environmental responses. However, information regarding their role in fruit development and ripening, a plant-speciﬁc process, is unknown. The present study seeks to determine whether and, if so, how sphingolipids are involved in fleshy-fruit development and ripening in an oil-crop species such as olive (Olea europaea L. cv Picual). Here, in the plasma membranes of live protoplasts, we used flourescence to examine various specific lipophilic stains in sphingolipid-enriched regions and investigated the composition of the sphingolipid long-chain bases (LCB) as well as the expression patterns of sphingolipid-related genes, OeSPT, OeSPHK, OeACER, and OeGlcCerase, during olive-fruit development and ripening. The results demonstrate increased sphingolipid content and vesicle trafficking in olive-fruit protoplasts at the onset of ripening. Moreover, the concentration of LCB [t18:1(8Z), t18:1 (8E), t18:0, d18:2 (4E/8Z), d18:2 (4E/8E), d18:1(4E), and 1,4-anhydro-t18:1(8E)] increases during fruit development to reach a maximum at the onset of ripening, although these molecular species decreased during fruit ripening. On the other hand, OeSPT, OeSPHK, and OeGlcCerase were expressed differentially during fruit development and ripening, whereas OeACER gene expression was detected only at the fully ripe stage. The results provide novel data about sphingolipid distribution, content, and biosynthesis/turnover gene transcripts during fleshy-fruit ripening, indicating that all are highly regulated in a developmental manner.